(untitled) (Ameghiniana, 2014)
"The ostracods found in the lower beds of the Collón Cura Formation, which is exposed in northwestern Chubut province, are described. Three species are mentioned for the first time for the strata and two taxa are proposed as new: Cyprinotus australis sp. nov. and Limnocfthere colloncurense sp. nov. Based on the presence of the genus Cuprinotue, which up to now was only mentioned from low latitudes, the inferred paleoenvironment had temperatures near 20°C; the limnic waters were mineralized and responded to the neutral saline path with carbonates (presence of Limnocythere), sulfates and chlorateso Taking into account global relative temperature changes along the Miocene, a probable Lower Miocene to early Middle Miocene age for the studied lower section of the Collón Cura Formation is thus confirmed."